Effects of seabuckthorn pomace on rumen development, intramuscular fatty acids and antioxidant capacity in weaned lambs - Diao, Xiaogao; Zhang, Xuanzi; Hao, Xiaoyan; Mu, Chuntang; Zhang, Jianxin (Frontiers in Veterinary Science, 2025)
Sea buckthorn pomace (SBP), a by-product derived from sea buckthorn fruit, is rich in nutrients and contains multiple pharmacologically active compounds. Consequently, SBP has the potential to serve as an alternative feed source for ruminants. This study aimed to evaluate the effects of SBP supplementation on organ weight, rumen development, intramuscular fatty acid composition, and antioxidant capacity in weaned lambs. Forty weaned Duper × Small-tailed Han lambs were randomly assigned to one of four dietary treatments in a completely randomized design. The experimental diets included 0% SBP (control), 8% SBP, 16% SBP, and 24% SBP, which were administered over an 80-day period. The results revealed that organ weight increased linearly with SBP supplementation, with the 16% SBP group demonstrating the highest weight gain (p < 0.05). Rumen and small intestine deposition exhibited a quadratic response, while omental fat accumulation was significantly greater in the SBP-supplemented groups compared to the control (p = 0.01). Additionally, rumen papilla length, width, and keratin layer thickness were positively influenced by SBP supplementation (p = 0.01). In rumen fluid, acetate, propionate, total volatile fatty acids, and acetate/propionate ratio showed a linear increase with SBP supplementation, whereas rumen pH displayed an inverse trend (p < 0.05). Marbling in longissimus dorsi improved in the SBP group along with enhanced meat quality parameters such as saturated fatty acid (TSFA), total monounsaturated fatty acid (TMUFA), and total polyunsaturated fatty acids (TPUFA), indicating that meat from lambs fed with 16% SBP was more tender and of better quality (p < 0.05). Furthermore, SBP also increased the antioxidant capacity of muscle tissue (p < 0.05). The above results indicate that adding SBP at a level of 16% in weaned lambs’ diets can enhance organ weight, promote ruminal development, improve meat quality, and provide antioxidant benefits. SBP can be included at up to 24% in weaned lambs’ diets without negative effects.